2006
DOI: 10.1103/physrevlett.97.147003
|View full text |Cite
|
Sign up to set email alerts
|

Commensurability Effects in Superconducting Nb Films with Quasiperiodic Pinning Arrays

Abstract: We study experimentally the critical depinning current Ic versus applied magnetic field B in Nb thin films which contain 2D arrays of circular antidots placed on the nodes of quasiperiodic (QP) fivefold Penrose lattices. Close to the transition temperature Tc we observe matching of the vortex lattice with the QP pinning array, confirming essential features in the Ic(B) patterns as predicted by Misko et al. [Phys. Rev. Lett. 95(2005)]. We find a significant enhancement in Ic(B) for QP pinning arrays in comparis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 24 publications
(41 reference statements)
3
77
0
Order By: Relevance
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 85%
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 85%
“…Recently antidot arrangements with a big variety of symmetries have been investigated. Matching effects have been reported in perforated Nb thin films for antidots lattices with short range order [12], or quasiperiodic fivefold Penrose structures [13]. Moreover asymmetric pinning arrays have been suggested as superconducting rectifiers [14].…”
mentioning
confidence: 99%
“…Nonetheless, this limitation of the actual microtrap configuration, which is caused by the exclusion of the magnetic flux from the niobium wire, can be overcome by using superconducting thin films [16] or superconducting microstructures with antidots [17]. These allow the penetration of magnetic flux and promise to support strong magnetic confinement for atom clouds with exceptional spin coherence times even at micron distances from the superconducting surface.…”
Section: Exceptionally Long Atomic Spin Coherence Near Superconductorsmentioning
confidence: 99%